The effect of post-transport electrolyte supplementation on the dressing-out percentage of cattle, tested under commercial conditions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology, at Massey University, Palmerston North, New Zealand - Ludbrook, Roger Samuel (Massey University, 1994)
The commercially used electrolyte supplement Multigro, was diluted with water and supplied to cattle as a dilute electrolyte solution. The cattle were being held in the lairage area of an export licensed meat works, and experienced normal commercial lairage conditions. The electrolyte solution was supplied to the cattle through the trough system in the lairage area. The aim of the experiment was to measure whether the cattle supplied the solution achieved a greater dressing out yield compared to cattle that were supplied water only in the lairage area. A total of 83 animals, made up of a combination of steers and bulls, were split into two treatment groups; cattle supplied water (W), (n = 41), and cattle supplied electrolyte (E), (n = 42). The cattle came from different commercial farms all within a 40 minute transportation journey of the meat plant. Two other experiments were also conducted, the first attempted to determine the water requirements of cattle in lairage. The second aimed to identify whether cattle preferred the electrolyte solution offered to water by offering both solutions to a group of cattle at the same time. The use of this electrolyte solution failed to improve the dressing-out percentage, under commercial conditions. It is suggested that the reason for this result was due to the failure of the animals to gain adequate rest while in lairage. It is further suggested that this inability to rest adequately meant that the animals never fully recovered from the influence of stressors affecting their behaviour in lairage, the result being the homeostatic control mechanism would still have been operative, assisting the animal in adjusting to its new surroundings, but not allowing its muscles to rehydrate and achieve a normal, rested, homeostatic balance.
Keywords: Meat cutting; Beef quality; Beef cattle -- Physiology; Colour of meat